Systemic review on fitness and survival of salmonella in dynamic environment and conceivable ways of its mitigation - Sutar, Ajit A.; Dashpute, Rohit S.; Shinde, Yashodhara D.; Mukherjee, Srestha; Chowdhury, Chiranjit (Indian Journal of Microbiology, 2024)
Gastroenteritis caused by non-typhoidal Salmonella still prevails resulting in several recent outbreaks affecting many people worldwide. The presence of invasive non-typhoidal Salmonella is exemplified by several characteristic symptoms and their severity relies on prominent risk factors. The persistence of this pathogen can be attributed to its broad host range, complex pathogenicity and virulence and adeptness in survival under challenging conditions inside the host. Moreover, a peculiar aid of the ever-changing climatic conditions grants this organism with remarkable potential to survive within the environment. Abusive use of antibiotics for the treatment of gastroenteritis has led to the emergence of multiple drug resistance, making the infections difficult to treat. This review emphasizes the importance of early detection of Salmonella, along with strategies for accomplishing it, as well as exploring alternative treatment approaches. The exceptional characteristics exhibited by Salmonella, like strategies of infection, persistence, and survival parallelly with multiple drug resistance, make this pathogen a prominent concern to human health.
Keywords: Antibiotic resistance; Gastroenteritis; Non-typhoidal Salmonella; pathogenesis; Plant-derived metabolites; Salmonella pathogenicity islands; Type III secretion system